The Impact of Organizational Citizenship on Job Performance of Employees in the Private Automotive Sector in Saudi Arabia in the light of 2030’s vision - Ali, Ahmed Farouk; Eid, Elsayed; Alhadad, Heba (Arab Journal for Sciences and Research Publishing, 2024)
The study aimed to explore the relationship between the development of Organizational Citizenship Behavior (OCB) and employee performance in the private automotive sector in the Kingdom of Saudi Arabia in light of Vision 2030. The study adopted a descriptive, analytical, and correlational methodology. A sample of 341 participants from five companies operating in the private automotive sector in the Kingdom of Saudi Arabia was selected. Although the study does not aim to establish a causal relationship between OCB and job performance, it acknowledges that enhancing this concept can contribute to the overall success of the organization.The effects of this study extend beyond the direct impact on job performance. Encouraging OCB can promote teamwork, collaboration, and knowledge sharing among employees, ultimately leading to improved organizational efficiency and effectiveness. The study's findings indicated a relationship between OCB, training, and job satisfaction. While the expected direct correlation between OCB and job performance was not confirmed, the analyses highlighted the significant and mediating role of training in enhancing job satisfaction. These insights enrich our understanding of the underlying mechanisms and suggest adopting training initiatives as a strategic means to foster job satisfaction and modulate the effects of OCB within organizational settings. It is recommended to promote a culture of OCB by enhancing behaviors beyond job tasks, investing in training to boost job satisfaction, and favoring initiatives to enhance overall employee satisfaction to improve performance.
Keywords: organizational citizenship behavior; job performance; private automotive sector; Saudi Arabia; employee behavior; organizational effectiveness